Influence of Foot Type on the Clinical Outcome of Minimally Invasive Surgery for Metatarsalgia. A Prospective Pilot Study - Naranjo-Ruiz, Carmen; Martínez-Nova, Alfonso; Canel-Pérez, María de los Ángeles; López-Vigil, Miguel; Ferrer-Torregrosa, Javier; Barrios, Carlos (Frontiers in Surgery, 2021)
Abstract Background and aims: Surgical procedures for central metatarsalgia seek to harmonise the metatarsal parabola with osteotomies that can be performed by minimally invasive techniques. However, the possible relationship of the foot type and the mid-term postoperative outcome is poorly described. The objective of this prospective pilot study was therefore to determine whether the foot type (pronate, neutral, or supinate) conditions the postoperative mid-term functional outcome. Methods: A series of 28 patients (6 men, 22 women) were treated for primary central metatarsalgia by means of minimally invasive distal metaphyseal osteotomy (DMMO). Results: Their functional outcomes at 6 and 12 months were assessed by the self-reporting AOFAS scale. Pre-surgery, the patients' scores were 42.82 ± 15.60. Scores improved at 6 months to 86.50 ± 8.6 and to 92.93 ± 8.6 at 12 months (p<0.001 in both cases). There were no differences either by sex or by foot type in these overall values, although there was only a slight limitation of interphalangeal mobility in the supinated feet (p=0.03) at 6-month follow-up as compared to other foot types. Conclusion: Hence, DMMO provides an optimal clinical and functional outcome for the surgical treatment of metatarsalgia, regardless of the patient's foot posture. The occurrence of adverse events was minimal and clinically irrelevant. Trial registration: The study was authorised by the Research Ethics Committee of the Universidad Católica de Valencia San Vicente Mártir, with the registry UCV/2018-2019/019.